NAVIGATING THE IMPLEMENTATION AND CHALLENGES OF LOCAL CONTENT CURRICULUM FOR RELIGIOUS EDUCATION AT MADRASAH IBTIDAIYAH - Nafi'ah, Siti Anisatun; Faoziah, Niswatin; Ngaini, Luluk Nurul; Khairunisa, Nurfita (Jurnal As Sibyan, 2024)
In recent years, many elementary schools/ Sekolah Dasar (SD) and Islamic primary schools/Madrasah Ibtidaiyah (MI) have depended primarily on the national curriculum. However, Madrasah Ibtidaiyah (MI) can benefit from adopting innovative curriculum models to strengthen its role in the community and create a strong brand identity. This study investigates the balance and consistency of a local curriculum grounded in diniyah (Islamic religious) education, analyzed through the Curricular Spider Web model. Using a qualitative case study approach, data were collected through semi-structured interviews with five teachers and a school principal and classroom observations. Data analysis was conducted through data condensation, display, and verification processes. The findings reveal that the curriculum at Madrasah Ibtidaiyah Ma’arif Nahdlatul Ulama Brunosari aligns well with the Spider Web model's components. However, challenges remain, particularly in the teacher’s role component, as some students continue to struggle with material mastery, indicating a need for further support and adaptation in curriculum delivery